Pentingnya Penggunaan Alat Pelindung Diri (APD) pada Pekerja Bangunan terhadap Keselamatan Kerja - Nurdiana Tanjung; Susilawati Susilawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Construction workers are often exposed to high risks of injury and illness due to potentially dangerous work environments. Therefore, the use of Personal Protective Equipment (PPE) is very important to protect them from various threats on construction sites. Literature research conducted in recent years has provided consistent evidence regarding the benefits and importance of using PPE in the construction industry. Various types of PPE, such as safety helmets, safety shoes, protective eyewear, respirators, and gloves, have been shown to be effective in reducing the risk of physical injury and exposure to hazardous materials. Literature studies also show that implementing strict policies related to the use of PPE can reduce the rate of work accidents and work-related illnesses. In addition, proper training and awareness of the importance of occupational safety have been proven to increase worker compliance with the use of PPE. Factors such as adequate availability of PPE, strict standards, a strong safety culture, supervision, and ongoing education are key elements in ensuring effective use of PPE and improving occupational safety in construction workplaces. Therefore, continued emphasis on the correct and consistent use of PPE is a must in efforts to maintain the safety and health of construction workers throughout the world.